Application Of Vikor Method To Determine The Location Of Election And Election Care Villages - Winda Amanda (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
General elections are the core of the democratic process which involves active community participation. In order to realize optimal participation, it is necessary to make efforts to increase public awareness and participation in elections and elections. One effective way is to identify strategic locations to implement the "Village Care for Elections and Elections" program. This study aims to apply the VIKOR method (VlseKriterijumska Optimizacija I Kompromisno Resenje) in determining the optimal location for the program. The VIKOR method is used as an analytical tool in considering several relevant criteria, such as the level of previous participation, the level of political awareness, the accessibility of the location, and the level of local government support. These data are evaluated and analyzed to assign a ranking to each potential location. Application steps include data collection, normalization, calculating VIKOR scores, and determining ranking. The results of this research provide clear guidance in determining the most suitable location for the "Election and Election Care Village" program. The selected location is the result of a compromise that considers all relevant criteria. It is hoped that the results of this research can become a basis for local governments or related institutions to allocate resources more effectively in order to increase people's participation in the democratic process.